Awareness of Paddy Growers regarding Neem Coated Urea in Davangere District - Raghuraja, J; Madhumathi, M (Journal of Agricultural Extension Management, 2018)
The study was conducted in Davangere district of Karnataka state using Expost-facto research design. One hundred paddy growers from 10 villages representing two taluks of the district constituted the sample for the study. The data were collected through personal interview method using structured interview schedule. The findings reveal that 57.00 per cent of paddy growers had heard about Neem Coated Urea (NCU), while 72.00 per cent of them were not aware of its benefits. Majority (69.00%) of the paddy growers did not use NCU in crop production and 88.00 per cent were not aware that less quantity of NCU is required for better crop production than usage of plain urea. Only 19.00 per cent of the growers felt that plain urea should be completely replaced by NCU. The results imply that extension personnel should play a larger role in creating awareness about NCU among the farming community. Higher the usage of NCU by the farmers, greater will be the savings for the national exchequer ensuring a win-win situation for both farmers and Government.